Computational simulation of low energy x-ray source for photodynamic therapy: a preliminary study - Leandro da Silva de Souza; Mirko Salomón Alva-Sánchez; Alexandre Bonatto (Brazilian Journal of Radiation Sciences, 2021)
Photodynamic therapy is a therapeutic modality capable of selectively inducing cytotoxic effects in malignant cells. Such effects are obtained by using a laser or a lamp as a light source to irradiate a previously-delivered photosensitizer into the tumoral cells. Since clinical application of photodynamic therapy depends on light penetration, lasers and lamps can only be used for shallow tissue treatment. To overcome this limitation, x-ray induced photodynamic therapy has been recently proposed. The goal of this work is to investigate the x-ray interactions in a medium containing a homogeneous concentration of distinct photosensitizers. This is achieved by evaluating the relative doses and energy spectra, obtained at distinct depths by means of Monte Carlo simulations. Preliminary results for the relative dose showed a minor dose increase, of approximately 0.15%, when photosensitizers are used. In addition, x-ray interactions with the investigated photosensitizers mostly occur from photons with energies below 60 keV.